Assessment on bioactive compounds and the effect of microwave on pitaya peel - Norashikin, Mat Zain; Muhd Azlan, Nazeri; Nurul Aini, Mohd Azman (Penerbit Universiti Teknologi Malaysia, 2019)
Over the years, a wide variety of natural colour sources have been identified. One source, the pitaya fruit is known to impart colours to products, such as food and drink. However, there have been limited studies done to determine phenolic compounds and antibacterial activity of the pitaya peel (H.polyrhizus) via Microwave Assisted Extraction (MAE) method. Both this information can escalate the potential role of pitaya fruit as a natural colour source. This study aimed to identify the types of bioactive compounds (phenolic compounds) and antibacterial activity of pitaya peel. To achieve this objective, MAE was used to extract bioactive compounds from the pitaya peel as it maintained the integrity of the compound. Based on the results, 13 types of phenolic compounds were identified from the pitaya peel extract via qualitative research using library database matching which include quinic acid, cinnamic acid, quinic acid isomer, 3,4-dihydroxyvinylbenzene, isorhamnetin 3-O-rutinoside, myricetin rhamno-hexoside, 3,30-di-O-methyl ellagic acid, isorhamnetin aglycone monomer, apigenin, jasmonic acid, oxooctadecanoic acid, 2 (3,4-dihydroxyphenyl)-7-hydroxy-5-benzene propanoic acid and protocatechuic hexoside conjugate. The pitaya peel extract was also found to have small antibacterial effect on the Gram-positive, Staphylococcus aureus (S.aureus) and Gram- negative, Escherichia coli (E.coli). The SEM demonstrated that cell wall disruption of pitaya peel caused by microwave radiation from MAE appeared to be the main reason for rapid extraction of bioactive compounds. In conclusion, the study established that pitaya peel extract is a natural colour source with an abundance of phenolic compounds and minimal antibacterial activity, which could be used in the food and cosmetic industries.